Management of women with endometriosis in the 21st century - Sardo; Attilio Di Spiezio; Becker, Christian M.; Renner, Stefan P.; Suvitie, Pia A.; Tarriel, Josep Estadella; Vannuccini, Silvia; Velasco, Juan A. Garcia; Verguts, Jasper; Mercorio, Antonio (LIPPINCOTT WILLIAMS & WILKINS, 2025)
Purpose of review
Endometriosis is a chronic inflammatory condition that significantly affects women’s quality of life and fertility. Despite advancements in treatment, many areas of uncertainty persist in clinical management. This review provides a symptom-focused, patient-centered update, addressing cases from asymptomatic to those complicated by pain and infertility
Recent findings
Advancement in imaging technology has increased incidental diagnoses of asymptomatic endometriosis, raising the debate between immediate treatment and watchful waiting. Medical therapy primarily aims to suppress symptoms, with oral gonadotropin-releasing hormone antagonists and add-back therapy offering promising long-term pain control. Research into local neurogenesis and central sensitization supports complementary approaches, though high-quality evidence is still limited. For pain refractory to medical therapy, conservative surgical strategies can minimize postoperative complications without significantly increasing recurrence rates. In infertility, assisted reproductive technology (ART) provides effective options, although the optimal endometrial preparation and the necessity of pre-ART surgery remain to be fully elucidated
Summary
The optimal management of endometriosis requires a personalized, multidisciplinary approach within specialized centers. Long-term suppressive medical therapy remains the cornerstone of pain management while emerging targeted agents hold promise for better symptom control with fewer side effects. Surgical intervention should be performed by experienced surgeons as a single definitive procedure when possible. Tailored ART protocols can address infertility challenges. Standardized classification systems and robust randomized trials are crucial to refining treatment pathways, optimizing fertility outcomes, and enhancing quality of life.